Congenital triangular alopecia with a tuft of normal hair inside. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
A 5-year-old girl was first observed for the presence of an apparently alopecic patch present on the scalp from the earliest stages of life. Since it was first noted the patch had not undergone significant changes. There were no similar cases in the family and personal and family history was negative for autoimmune diseases. Physical examination showed in the left frontal region a roughly triangular patch with the front base of about 3 cm (Fig. 1). The underlying skin was normal and provided with thin hair, as confirmed by dermoscopic observation (Fig. 2). Inside the patch near its front edge there was a tuft of hair of normal thickness (Fig. 1 circled and Fig. 3 on dermoscopy). The final diagnosis was congenital triangular alopecia with a tuft of normal hair inside.